ANALISIS MOTIF DAN DAMPAK PENGGUNAAN APLIKASI TINDER BERBAYAR - Anziela Paramitha; Steven Tanuwijaya; Susilowati Natakoesoemah (Universitas Tidar, 2021)
Today's rapid technology development has created more advanced social media applications, such as Tinder. Tinder benefits its user with just a click away from finding their